Exploring the pharmacokinetics of phenoxymethylpenicillin (Penicillin-V) in adults: a healthy volunteer study - Rawson,TM; Wilson,R; Moore,L; Macgowan,A; Lovering,A; Bayliss,M; Kyriakides,M; Gilchrist,M; Roberts,J; Hope,W; Holmes,A (Open Forum Infectious Diseases, 2021)
This healthy volunteer study aimed to explore Phenoxymethylpenicillin (Penicillin-V) pharmacokinetics (PK) to support the planning of large, dosing studies in adults. Volunteers were dosed with penicillin-V at steady state. Total and unbound penicillin-V serum concentration was determined and a base population PK model were fitted to the data.